PELATIHAN (WORKSHOP) DAN SOSIALISASI MENGENAI TANAMAN HIDROPONIK DI KELURAHAN KEBON PALA KOTA ADMINISTRASI JAKARTA TIMUR TAHUN 2021 - Grace Putri Dianty; Array Evangelista Nanjan; Maria Febronia Penate Boik; Dea Cosella; Ulinata Ulinata (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2021)
The Architecture Study Program of Faculty of Engineering Universitas Kristen Indonesia carried out Community Service activities by continuing the previous Community Service activities with the theme Green Action 23: Training (Workshop) and Socialization Regarding Hydroponic Plants in Kebon Pala Village, East Jakarta City Administration in 2021 which was previously held only in RW 09 just. This Community Service activity aims to provide education about how to grow hydroponics, and what are the benefits of growing hydroponics. The method used is to hold a Training (Workshop) and Socialization about hydroponic plants by inviting resource persons who are experts in the field of hydroponics so that participants receive education about how to grow hydroponics, and what are the benefits of growing hydroponics that participants are expected to be able to independently plant hydroponics and transmit it to neighbors in the neighborhood, relatives, family and relatives. The process is by direct practice to the participants using the tools and materials that will be provided including the nutrient tub and hydroponic tub cover, nutrient fertilizer AB mix Puriegarden, Nutrient Measuring Injections, Seeds, Wicked Netpot, Gauze, Toothpick, Hose, Wicked Netpot, Airator, Cut flannel, Rockwool, TDS which were distributed to the participants by giving a question and answer session to the participants who needed further explanation.